TINJAUAN SISTEM PENDAFTARAN PASIEN RAWAT INAP DI RSU MITRA SEJATI MEDAN - Suheri Parulian Gultom; Febri Yani Friska Ginting (Akademi Perekam dan Informasi Kesehatan Imelda, 2020)
Patient registration is the foremost part of Hospital service, because the patient registration records the identity and requirements of his visit to the hospital, and at the time of registration the patient gets the first impression of the hospital's services. The purpose of this study was to determine the stages of admission of inpatients at Mitra Sejati Hospital Medan and to find out the obstacles in the implementation of inpatient admissions at Mitra Sejati Hospital in Medan in 2017. The type of research used is descriptive using a quantitative approach, the research sample is 5 inpatient registration officers, data collection was done by interviewing the inpatient registration officer. The results showed that the registration stages of inpatients at Mitra Sejati Hospital Medan had not met the regulations of the PERMENKES (2008) on the naming and use of KIB and KIUP. It can be concluded that Mitra Sejati Hospital Medan has not implemented the naming rules according to the PERMENKES and has not implemented the use of KIB and KIUP. It can be suggested that registration officers should have implemented a naming system according to the PERMENKES rules and already have to implement the use of KIB and KIUP to make it easier for officers to register patients and find patient medical record files. For education, to explain more to students how the stages of inpatient registration are. For inpatient registration officers at Mitra Sejati Hospital Medan, it is better if they need to carry out training on the stages of patient acceptance / registration to improve a more effective way of working.Patient registration is the foremost part of Hospital service, because the patient registration records the identity and requirements of his visit to the hospital, and at the time of registration the patient gets the first impression of the hospital's services. The purpose of this study was to determine the stages of admission of inpatients at Mitra Sejati Hospital Medan and to find out the obstacles in the implementation of inpatient admissions at Mitra Sejati Hospital in Medan in 2017. The type of research used is descriptive using a quantitative approach, the research sample is 5 inpatient registration officers, data collection was done by interviewing the inpatient registration officer. The results showed that the registration stages of inpatients at Mitra Sejati Hospital Medan had not met the regulations of the PERMENKES (2008) on the naming and use of KIB and KIUP. It can be concluded that Mitra Sejati Hospital Medan has not implemented the naming rules according to the PERMENKES and has not implemented the use of KIB and KIUP. It can be suggested that registration officers should have implemented a naming system according to the PERMENKES rules and already have to implement the use of KIB and KIUP to make it easier for officers to register patients and find patient medical record files. For education, to explain more to students how the stages of inpatient registration are. For inpatient registration officers at Mitra Sejati Hospital Medan, it is better if they need to carry out training on the stages of patient acceptance / registration to improve a more effective way of working.